Analysis Of Work Motivation, Work Discipline, And Work Ability On Employee Performance At PT Perkebunan Nusantara IV Medan - Dina Nopita Muliawati; Wilchan Robain; Teguh Teguh (Universitas Dehasen Bengkulu, 2026)
This study was conducted to examine the influence of work motivation, work discipline, and work ability on employee performance at PT Perkebunan Nusantara IV in Medan. The research object consists of employees working at the company. The study was carried out during the period of 2025–2026. The population as well as the research sample consisted of 76 respondents. Data processing was performed using IBM SPSS Statistics 24. The analytical techniques applied in this study included classical assumption testing and multiple linear regression analysis. The findings indicate that the t-test for the work motivation variable (X1) produced a t-value of 2.072, which is greater than the t-table value of 1.993, with a significance level of 0.042 (< 0.05). This result shows that work motivation has a positive and significant partial effect on employee performance. Furthermore, the t-test for the work discipline variable (X2) yielded a t-value of 5.537, which exceeds the t-table value of 1.993, with a significance value of 0.000 (< 0.05). This indicates that work discipline also has a positive and significant partial influence on employee performance. Similarly, the t-test for the work ability variable (X3) resulted in a t-value of 2.084, which is higher than the t-table value of 1.993, with a significance value of 0.041 (< 0.05). This demonstrates that work ability partially has a positive and significant effect on employee performance. In addition, the F-test results show an F-value of 35.741, which is greater than the F-table value of 3.12, with a significance level of 0.000 (< 0.05). This finding indicates that work motivation, work discipline, and work ability simultaneously have a significant effect on employee performance. The coefficient of determination (R²) obtained is 0.582 or 58.2%, which means that the variables of work motivation, work discipline, and work ability are able to explain 58.2% of the variation in employee performance, while the remaining 41.8% is influenced by other variables outside this study.